2022
DOI: 10.1101/2022.07.28.22278151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indoor air pollutants and respiratory outcomes among residents of an informal urban setting in Uganda: a cross-sectional study

Abstract: Background Indoor air pollutants (IAP) such as particulate matter (PM) and carbon monoxide (CO) are a leading cause of acute respiratory symptoms, and long-term health impacts such as respiratory diseases, heart diseases and cancers. In Uganda, literature on the effects of IAP on respiratory outcomes in informal settlements is limited. This study investigated the association of selected IAPs and cooking fuels with respiratory symptoms among children and adults. Methods This study was conducted among 284 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…This is a secondary analysis of the main study which assessed the effect of indoor air quality on health outcomes. The sample size calculated was for the main study based on the prevalence of respiratory problems (main outcome)(p) at 19.4%, 80% power, 5% power and 15% non-response rate but this sample size still had acceptable power for this secondary objective [ 30 ]. A representative sample of households were selected from the three parishes in Bwaise.…”
Section: Methodsmentioning
confidence: 99%
“…This is a secondary analysis of the main study which assessed the effect of indoor air quality on health outcomes. The sample size calculated was for the main study based on the prevalence of respiratory problems (main outcome)(p) at 19.4%, 80% power, 5% power and 15% non-response rate but this sample size still had acceptable power for this secondary objective [ 30 ]. A representative sample of households were selected from the three parishes in Bwaise.…”
Section: Methodsmentioning
confidence: 99%
“…Previous FRESH AIR studies have shown significant exposure to HAP and high prevalence rates of COPD in rural communities in the Kyrgyz Republic and Uganda 151,152 . Additionally, in Uganda, HAP was independently associated with asthma and persistent (childhood) cough [153][154][155] . Females and children are mostly exposed to HAP 156,157 .…”
Section: Air Pollution Exposurementioning
confidence: 99%
“…119 Additionally, some related studies have been done which could be points of comparison, including indoor air pollution levels in Vietnam 120 and Uganda. 121 Our study could be refined by using available data specific to Uganda and Vietnam. However, data for the same settings that covers the multiple dimensions in our analysis (e.g.…”
Section: Strengths and Limitationsmentioning
confidence: 99%